Wild versus lab house mice: Effects of age, diet, and genetics on molar geometry and topography. Issue 1 (1st August 2021) - Savriama, Yoland; Romestaing, Caroline; Clair, Angéline; Averty, Laetita; Ulmann, Julie; Ledevin, Ronan; Renaud, Sabrina
Abstract: Molar morphology is shaped by phylogenetic history and adaptive processes related to food processing. Topographic parameters of the occlusal surface, such as sharpness and relief, can be especially informative regarding diet preferences of a species. The occlusal surface can however be deeply modified by wear throughout an animal's life, potentially obliterating other signals. Age being difficult to assess in wild populations, especially small rodents, experimental studies of wear through age in laboratory populations may constitute a powerful way to assess its impact on molar geometry and topography, and to validate descriptors of molar morphology that could mitigate this issue. Molar morphology was therefore quantified using 3D geometric morphometrics and topographic estimates in four groups of house mice: wild‐trapped mice, lab‐bred offspring of these wild mice, typical laboratory mice, and their hybrids. Three descriptors of the molar morphology were considered: the surface of the whole molar row, the surface of the first upper molar, and a truncated template of the first upper molar mimicking advanced wear. Increasing wear with age was demonstrated in the different groups, with a more pronounced effect in the wild‐trapped population. The geometry of the molar row is not only modified by wear, but also by the relative position of the late developing molars on the jaw due to loading during mastication. As a consequence, the alignment of the molars is modified in wild mice, showing a qualitative difference between wild animals and their lab‐bred offspring. Results obtained from the lab should thus be transferred with caution to the interpretation of differences in wild populations. Topographic estimates computed for the first upper molar seems to provide more stable parameters than those based on the whole molar row, because issues related to non‐planar occlusal surface along the molar row are discarded. The truncated template was proven efficient in discarding the wear effect to focus on genetic differences, allowing an efficient characterization of the hybridization signature between wild and lab mice. Dominance of the wild phenotype for the first molar shape supports that the lab strain evolved in a context of relaxation of the selective pressures related to nutrition. Abstract : The geometry of the molar row was compared between wild‐trapped mice, their lab offspring, a typical lab strain, and their hybrids. The alignment of the three molars is perturbed in wild mice due to increased masticatory loading. Cusp abrasion due to wear is also most pronounced in wild mice, causing decrease in sharpness, relief, and slope. Genetic differences between wild mice and the lab strain are best displayed when focusing on tooth parts unaffected by wear.